Simulation-Based Microeconomics Learning: A Quasi-Experimental Study Using Simcity Games - Sugiono (Educational Researcher Journal, 2025)
This study aims to measure the effectiveness of the use of SimCity simulation games as an interactive learning medium in improving students' understanding of the concept of trading in Microeconomics courses. The method used is a quantitative approach with a quasi-experimental design, namely one-group pretest- post-test. The research subjects consisted of 14 students who participated in intervention learning using SimCity, where they experienced firsthand the process of contextual economic decision-making in a simulation of urban development. Data collection was carried out through an initial test (pretest) and a final test (post-test) to measure the level of student understanding before and after the intervention. The data were analyzed using a statistical test paired with a sample t-test to determine the significance of the difference in values. The results of the analysis showed that the average pretest score was 15.3 and increased to 18.7 in the post-test. The t-test yielded a significance value (p) of 0.000 (p < 0.05), which means that there was a statistically significant improvement. The conclusion of this study is that the use of SimCity has been shown to be effective in improving students' understanding of the concept of commerce. Simulation games provide a contextual, reflective learning experience and encourage critical thinking and cognitive engagement. However, the limitations of this study lie in the non-use of the control group and the relatively small number of participants. Further research is recommended to adopt a full experimental design with a larger sample count and a more diverse material context.